Antibacterial and Antibiofilm Potential of Leptospermum petersonii F.M.Bailey, Eucalyptus citriodora Hook., Pelargonium graveolens L'Hér. and Pelargonium roseum (Andrews) DC. Essential Oils Against Selected Dental Isolates. Issue 2 (4th March 2021) - Marinkovic, Jelena; Markovic, Tatjana; Nikolic, Biljana; Soldatovic, Ivan; Ivanov, Marija; Ciric, Ana; Sokovic, Marina; Markovic, Dejan
Abstract: The study aimed to investigate the potency of Leptospermum petersonii, Eucalyptus citriodora, Pelargonium graveolens, and Pelargonium roseum essential oils (EOs) against Streptococcus sanguinis and Streptococcus salivarius dental isolates. To examine the variation in sensitivity among strains of different origin, isolates from symptomatic and asymptomatic root canal infections, as well as the reference, strains S. sanguinis ATCC 10556 and S. salivarius ATCC 9222 were used in the study. EOs were chemically characterised (GC/MS). Their antibacterial and antibiofilm properties were detected by microdilution and CV assay respectively. Statistical analysis was performed by One way ANOVA. Examined bacterial strains, regardless clinical or ATCC, exhibited the highest sensitivity to L. petersonii and E. citriodora EOs (MIC ranged 0.53±0.00 - 5.88±1.27 mg/ml and 0.08±0.03 - 9.37±1.25 mg/ml respectively), while two other EOs were less efficient. Comparison of MIC values showed that sensitivity of the isolates recovered from symptomatic infections was the least, while the susceptibility of asymptomatic isolates and especially of reference strains were higher. EO inhibition of biofilm formation differed between clinical isolates of S. salivarius and their reference strain. Inhibition was higher in the case of S. salivarius ATCC 9222 (84 %-89 %) in comparison to that of clinical isolates (24 %-75 %). Regardless of the strains tested, E. citriodora exhibited the highest antibiofilm potential. To conclude: L. petersonii induced notable antibacterial potential, while E. citriodora EO proved promising antibacterial and antibiofilm activity. Due to the variable sensitivity of the isolates to EOs, it is suggested to screen activity on a large number of strains, especially from symptomatic infections.